2005
DOI: 10.1158/0008-5472.can-05-1891
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-6 Promotes Osteoblastic Prostate Cancer Bone Metastases through a Dual Mechanism

Abstract: Prostate cancer frequently metastasizes to bone where it forms osteoblastic lesions through unknown mechanisms. Bone morphogenetic proteins (BMP) are mediators of skeletal formation. Prostate cancer produces a variety of BMPs, including BMP-6. We tested the hypothesis that BMP-6 contributes to prostate cancer-induced osteosclerosis at bone metastatic sites. Prostate cancer cells and clinical tissues produced BMP-6 that increased with aggressiveness of the tumor. Prostate cancer-conditioned medium induced SMAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
145
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(155 citation statements)
references
References 68 publications
8
145
0
2
Order By: Relevance
“…7,19 Taken together, these lines of evidence suggest that BMP-6, noggin and sclerostin might be involved in a complex regulatory mechanism orchestrating the transformation, aggressiveness and bone metastatic ability of prostate cancer. In this study, we examined the expression level of BMP-6, noggin and sclerostin in 136 human prostate specimens by immunohistochemistry and investigated their prognostic significance in our prostate cancer patient cohort (n ¼ 95).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…7,19 Taken together, these lines of evidence suggest that BMP-6, noggin and sclerostin might be involved in a complex regulatory mechanism orchestrating the transformation, aggressiveness and bone metastatic ability of prostate cancer. In this study, we examined the expression level of BMP-6, noggin and sclerostin in 136 human prostate specimens by immunohistochemistry and investigated their prognostic significance in our prostate cancer patient cohort (n ¼ 95).…”
mentioning
confidence: 97%
“…14 Noggin has been shown to modulate the invasiveness and the osteoblastic activity of prostate cancer cells. 7,15 Overexpression of noggin in prostate cancer cells results in decreased ability of the cells to form osteolytic or osteoblastic lesions in tibias of immunosuppressed mouse. 16,17 Another study has shown that expression of noggin is an important determinant to decide whether a metastatic lesion is osteoblastic or osteolytic in nature.…”
mentioning
confidence: 99%
“…For example, androgen withdrawal-induced marked downregulation of relaxin, VEGF, vimentin and BMP-6, involved in cancer progression (Soker et al, 2001;Dai et al, 2005;Thompson et al, 2006;Feng et al, 2007;Wei et al, 2008) as well as upregulation of cellular retinol binding protein 7 and interferon-g receptor, negatively regulating cancer progression (Kuppumbatti et al, 2001;Yang et al, 2008), in LNCaP/IL-6#1. In addition, DnaJ, acting as a cytoprotective chaperon in response to stress-induced apoptosis (Cajo et al, 2006), were upregulated in LNCaP/IL-6#1, which might be an adaptive change as observed in Akt and MAPK pathways after androgen deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, expression levels of some genes associated with the progression of prostate cancer, such as relaxin, vascular endothelial growth factor (VEGF), vimentin and bone morphogenetic protein-6 (BMP-6) (Soker et al, 2001;Dai et al, 2005;Thompson et al, 2006;Feng et al, 2007;Wei et al, 2008), were significantly downregulated in LNCaP/IL-6#1 compared with LNCaP/Co. Overall, there are several genes listed in Table 1, which are known to have functions mediating cell growth, apoptotsis, and tumorigenesis, showing expression profiles that are reasonable for theoretically elucidating the molecular mechanism mediating enhanced sensitivity to androgen withdrawal by overexpression of IL-6.…”
Section: Effects Of Interleukin-6 Secretion On Prostate Cancer T Teramentioning
confidence: 99%
“…High levels of BMP-6 signaling, a consequence of its increased expression and the decreased expression of its inhibitors, might promote the development of PCa metastases (Yuen et al, 2008). This growth factor may have a direct inductive role in PCa-associated bone metastases (Dai et al, 2005). The increased metastatic potential promoted by BMP-6 is at least in part because of the increase in metaloproteinases and Id-1 (Darby et al, 2008), a downstream BMP target that was previously shown to be indicative of a worse prognosis in earlystage cervical cancer and epithelial ovarian tumors (Schindl et al, 2001;.…”
Section: Tgf-βmentioning
confidence: 99%